2012
DOI: 10.1371/journal.pone.0051996
|View full text |Cite
|
Sign up to set email alerts
|

Enterovirus 71-Induced Neurological Disorders in Young Gerbils, Meriones unguiculatus: Development and Application of a Neurological Disease Model

Abstract: A reliable disease model mimicking Enterovirus 71 (EV71) infection in humans is essential for understanding pathogenesis and for developing a safe and effective vaccine. Commonly used rodent models including mouse or rat models are not suitable for vaccine evaluation because the rodents are resistant to EV71 infection after they reach the age of 6 days. In this study, 21-day-old gerbils inoculated intraperitoneally (IP) with a non mouse-adapted EV71 strain developed neurological lesion-related signs including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 30 publications
(45 reference statements)
1
37
0
Order By: Relevance
“…Additionally, angiomotin-like protein 2 (AMOTL2) and two other members of the motin family are the Yes-associated protein 1 (YAP1)-associated proteins, which regulate the expression of several proliferation- and apoptosis-related genes. It has been reported that AMOTL2 is essential for cell movements in vertebrate embryos [56] and serves as a scaffolding protein to regulate Wnt/β-catenin [7]. In addition, the phosphate cytidylyltransferase 2 ( PCYT2 ) gene was 3.5-fold up-regulated during EV71 infection in SH-SY5Y cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, angiomotin-like protein 2 (AMOTL2) and two other members of the motin family are the Yes-associated protein 1 (YAP1)-associated proteins, which regulate the expression of several proliferation- and apoptosis-related genes. It has been reported that AMOTL2 is essential for cell movements in vertebrate embryos [56] and serves as a scaffolding protein to regulate Wnt/β-catenin [7]. In addition, the phosphate cytidylyltransferase 2 ( PCYT2 ) gene was 3.5-fold up-regulated during EV71 infection in SH-SY5Y cells.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse experiments revealed that EV71 invaded the CNS through retrograde axonal transport and that hematogenous transport represented only a minor route of transmission [4], [5], [6]. Histopathological changes, such as neuronal degeneration, neuronal loss and neuronophagia, were observed in the spinal cord, brainstem, and skeletal muscle, along with necrotizing myositis and splenic atrophy, after gerbils were inoculated intraperitoneally with EV71 [7]. Additionally, radiological or histopathological evidence of the induction of paralysis, a similar process to that of poliovirus, was also observed during EV71 infection [8], [9], [10], [11].…”
Section: Introductionmentioning
confidence: 99%
“…In cases that resemble poliomyelitis, widespread neuronal necrosis is the dominant histopathological feature associated with the replication of this virus in neurons and results in the clinical manifestation of neurogenic paralysis (Whitton et al, 2005). Although several autopsy findings have suggested that EV71 may infect neurons and cause the neuronal degeneration observed in individual fatal HFMD cases (Khong et al, 2012; Yao et al, 2012), the mechanism underlying the neuronal pathogenesis in the CNS has not been described in the literature. This situation has raised the question of how the pathological progression caused by the EV71 infection leads to the severe clinical manifestations (such as neurogenic pulmonary edema and cardiopulmonary failure) that are responsible for the high case fatality rate (Chan et al, 2000; Wu et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…M. unguiculatus infected with Helicobacter pylori mimic human H. pylori infection, facilitating the analysis of the underlying processes and the study of gastritis and gastric cancer (Wei et al, 2012). M. unguiculatus has also been used in studies of nutrition (Ying et al, 2013), aging (Ohlemiller, 2009), epilepsy (Heo and Kang, 2012), parasites (Conchedda et al, 2006), ethology (Moons et al, 2012), and viral infections (Yao et al, 2012). However, although it is an important experimental animal, the available genetic information on gerbils is very limited and its phylogenetic classification is uncertain.…”
Section: Introductionmentioning
confidence: 99%